Deixis Reflected in The Grammarly Advertisement Video Script - Wiryawan, Melanie Gywett (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Advertisements are crafted to influence and engage audiences through various linguistic strategies. This study investigates the use of deixis in a Grammarly advertisement video, focusing on how different types of deictic expressions contribute to the narrative and effectiveness of the advertisement. Using Levinson's (1983) framework, the research categorizes deictic expressions into five types: person, place, time, discourse, and social deixis. The qualitative content analysis reveals that person deixis helps establish character identities and relationships, while place deixis provides spatial context, enhancing the audience's ability to visualize scenes. Time deixis ensures chronological coherence and builds suspense, and discourse deixis maintains narrative continuity and focus. Social deixis highlights social relationships and hierarchies, adding depth to interactions. The findings underscore the importance of contextual information in interpreting deictic expressions and demonstrate how deixis enhances communication in advertising. This study contributes to the understanding of Pragmatic language use in promotional content and offers practical insights for creating more engaging and effective advertisements.